2013
DOI: 10.3402/tellusb.v65i0.19251
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying recycled moisture fraction in precipitation of an arid region using deuterium excess

Abstract: Terrestrial moisture recycling by evapotranspiration has recently been recognised as an important source of precipitation that can be characterised by its isotopic composition. Up to now, this isotope technique has mainly been applied to moisture recycling in some humid regions, including Brazil, Great Lakes in North America and the European Alps. In arid and semi-arid regions, the contribution of transpiration by plants to local moisture recycling can be small, so that evaporation by bare soil and surface wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
107
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(124 citation statements)
references
References 23 publications
(32 reference statements)
5
107
0
1
Order By: Relevance
“…Accordingly, d-excess is used to constrain both the source of precipitation and the conditions during vapor transport [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, d-excess is used to constrain both the source of precipitation and the conditions during vapor transport [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Hou et al, 1999;Yao et al, 1999;Zhang et al, 2003;Pang et al, 2011;Feng et al, 2013;Kong et al, 2013). This region provides an important platform to investigate hydrological processes occurring in an endorheic drainage basin in an arid climate; a good understanding of the isotopes in rainfall of the region is helpful for paleoclimate reconstruction using ice cores and speleothems as well as local water resource management during water shortages.…”
Section: Introductionmentioning
confidence: 99%
“…In arid central Asia, the existing isotopic studies showed that the hydrogen and oxygen isotopes in precipitation were mainly controlled by air temperature (also known as temperature effect), instead of precipitation amount (Yao et al, 1999;Feng et al, 2013;Liu et al, 2014). The extremely arid condition may influence below-cloud secondary evaporation and local moisture recycling (Pang et al, 2011;Kong et al, 2013).…”
Section: Introductionmentioning
confidence: 97%